Post-piracy care for seafarers guidelines - Brewer, Oliver (Актуальні проблеми транспортної медицини, 2011)
Today piracy has become a serious problem in maritime security. The threat of an attack, fight with the pirates and especially captivity cause psycho-emotional stress, lead to a breach of psychosomatic health and a threat to the lives of seafarers.